The implementation of comics strip in teaching recount text - Musfira, Musfira; Dardjito, Hanandyo; Akbar, Aditya Sahrul (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to describe the implementation of comic strips in teaching recount text writing to eighth-grade students of MTS Nurul Jamil Bombana based on a scientific approach. The research was conducted in Class VIII A. This study was action research. It was conducted in two cycles, from 8th April to 14th April 2021. The steps of the research were reconnaissance, planning, action and observation, and reflection. The subjects of the research were 20 students of the VIII A class. The data collected were in the form of qualitative data. The qualitative data were gained from observation, interviews, and documents. There were four steps in analysing the data: Data collection, data reduction, data display and conclusion/verification. The result of the research indicated that the implementation of Comic Strips based on the scientific approach was effective, and the comic strip improved the students’ learning process in writing recount texts. The students could generate ideas, and they could write recount texts in the correct form based on the criteria of effective writing skills.